2014
DOI: 10.1542/peds.2013-3077
|View full text |Cite
|
Sign up to set email alerts
|

Intellectual, Behavioral, and Emotional Functioning in Children With Syndromic Craniosynostosis

Abstract: WHAT'S KNOWN ON THIS SUBJECT: Children who have syndromic craniosynostosis are at risk for developing intellectual disability, behavioral and emotional problems. Study results were often based on small samples and wide age-based variation, using nonvalidated instruments and describing no clear inclusion and exclusion criteria.WHAT THIS STUDY ADDS: Intellectual, behavioral, and emotional functioning is described in a national sample (N = 82) of schoolaged children with syndromic craniosynostosis. Using standard… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
68
1
7

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(78 citation statements)
references
References 33 publications
2
68
1
7
Order By: Relevance
“…As in patients with sagittal craniosynostosis in whom altered DTI parameters may underlie their neuropsychological deficits, 37 WM abnormalities of the cingulate gyrus and corpus callosum in syndromic patients with craniosynostosis syndromes may be responsible for existing attention and memory problems. 14 However, neurologic assessment of our patients with craniosynostosis syndromes cannot explain diffusivity abnormalities in the corticospinal tracts, and motor deficits might rather be caused by impair-ment of the frontal WM. 38 Remarkably, the fornix seems to be spared by the mechanical pressure or stretching caused by ventriculomegaly and altered brain shape.…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…As in patients with sagittal craniosynostosis in whom altered DTI parameters may underlie their neuropsychological deficits, 37 WM abnormalities of the cingulate gyrus and corpus callosum in syndromic patients with craniosynostosis syndromes may be responsible for existing attention and memory problems. 14 However, neurologic assessment of our patients with craniosynostosis syndromes cannot explain diffusivity abnormalities in the corticospinal tracts, and motor deficits might rather be caused by impair-ment of the frontal WM. 38 Remarkably, the fornix seems to be spared by the mechanical pressure or stretching caused by ventriculomegaly and altered brain shape.…”
Section: Discussionmentioning
confidence: 76%
“…4,[9][10][11][12][13] Patients with craniosynostosis syndromes have a 2-fold higher risk for de-veloping intellectual disability than the normative population, while they also have more behavioral and emotional functioning problems. 14 In this study, we investigated whether diffusion tensor imaging and fiber tractography (FT) can be used for studying WM organization in patients with craniosynostosis syndromes. This technique should give more objective and anatomically complete information about WM tracts than the subjective single ROI approach that has been used before, 7 because parameters will be defined over the total length of a particular WM tract rather than at 1 certain location in the tract.…”
mentioning
confidence: 99%
“…It was found that there was no significant difference between GCA and NVC scores and all the children achieved a NVC score within the normal range. It is important to note the fact that this study used the british Ability Scales which are less demanding in terms of attention and fine motor skills than other assessments such as the Wechsler Intelligence Scale (maliepaard, mathijssen, Oosterlaan, & Okkerse, 2014). This might help explain the findings of Lefebvre et al (1986) who reported that children with Apert syndrome had lower verbal intelligence scores than their overall performance scores (using the Wechsler Intelligence Scale for Children (WISC)).…”
Section: Speech Language and Cognitive Developmentmentioning
confidence: 96%
“…Lajeunie et al, 1999;maliepaard et al, 2014;Patton et al, 1988). In a more recent study of 18 people with Apert syndrome (yacubian-Fernandes et al, 2004) aged between one year and 26 years, with an average of eight years, assessments on developmental or cognitive functions were correlated with the age of the patient, age at which cranial surgery was performed, brain development and quality of family environment.…”
Section: Speech Language and Cognitive Developmentmentioning
confidence: 99%
“…Agenesis of the corpus callosum (12-50%), anomalies of the septum pellucidum (24% PMID) and hydrocephalus (33.3%) may be present [37,40].…”
Section: Central Nervous System Malformationsmentioning
confidence: 99%